Pelatihan Pengolahan Hasil Laut Menjadi Produk Kaya Gizi dan Kekinian di Kub Mina Sejahtera Desa Penjajap Kecamatan Pemangkat Kabupaten Sambas - Nelly Wahyuni; Endah Sayekti; Titin Anita Zaharah; Risa Nofiani; Gusrizal Gusrizal (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
Penjajap Village, Pemangkat District, Sambas Regency, West Kalimantan is located near the sea. Most of the population are fishermen, either small or medium fishermen. Currently, the village has a joint cooperative, namely KUB Mina Sejahtera Penjajap Village. This cooperative fosters fisherwomen who process processed seafood such as meatballs, frozen meatballs, and nuggets. In order to fulfil nutrition and increase the selling value of marine products, it is necessary to diversify into processed products with complete and contemporary nutritional value. This activity aims to provide training on making dim sum that has complete nutritional content, namely protein, fibre, vitamins, and carbohydrates, and is a contemporary food with a high selling value. The implementation of community service is carried out using the community development method, namely community involvement starting from problem identification and program implementation. In addition, educational methods are used, namely socialization, training and mentoring approaches, as a means of knowledge transfer and education for community empowerment. The evaluation of the activities was carried out using a questionnaire which showed that the participants very much awaited the dim sum-making training because this processed food is very popular, easy to work with, can be applied directly both for daily menus that have complete nutritional content, and has the potential to be sold.